The Effect of Regional Original Revenue, GDP, and Capital Expenditure on Regency/City Fiscal Distress in South Sulawesi - Amrisal, Amrisal; Mallongi, Syahrir; Selong, Abbas (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2024)
This study was conducted with the following objectives: (1) To Determine and Analyze the Effect of PAD on Regency/City Fiscal distress in South Sulawesi. (2) To Determine and Analyze the Effect of GDP on Fiscal distress of Regencies/Cities in South Sulawesi, (3). To Determine and Analyze the Effect of Capital Expenditure on Regency/City Fiscal Distress in South Sulawesi. The research method used in this study is descriptive analysis and Panel data regression analysis, with a sample of 24 city districts in South Sulawesi. Based on the results of the regression analysis of panel data, the results of the study show that (1). PAD has a negative and significant effect on fiscal distress with a coefficient value of -1.303, meaning that if regional original revenue increases by 1%, fiscal distress will decrease by 1.303%. A negative Coefficient value indicates that there is a negative or opposite relationship between PAD (X1) and fiscal distress (Y). This means that if PAD increases, fiscal distress will decrease. (2) (GDP) has a negative and significant effect on fiscal distress with a coefficient value of -637547.3, meaning that if economic growth increases by one-unit, fiscal distress will decrease by 637547.3 units. (3). Capital expenditure has a negative effect on fiscal distress, with a coefficient value of -0.199, meaning that if the capital expenditure ratio increases by 1%, fiscal distress will decrease by 0.199%. This negative Coefficient value indicates that there is a negative relationship between capital expenditure (X3) and fiscal distress (Y). This means that if capital expenditure increases, fiscal distress will decrease.